Reproductive Health Problems Among the Adolescent Girls - Afrin, S; Rahman, MR; Rahman, M; Jahan, AA; Zaman, UKS; Rahman, N; Rahman, S (Bangladesh Medical Journal, 2011)
DOI: 10.3329/bmj.v39i2.7032 Bangladesh Medical Journal 2010, 39(2) pp.22-25